2023
DOI: 10.1097/qco.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

Host microbiome-pathogen interactions in pediatric infections

Abstract: Purpose of review In this review, we discuss recent research that has furthered our understanding of microbiome development during childhood, the role of the microbiome in infections during this life stage, and emerging opportunities for microbiome-based therapies for infection prevention or treatment in children. Recent findings The microbiome is highly dynamic during childhood and shaped by a variety of host and environmental factors. In turn, the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…Traditionally, these diseases have been attributed solely to pathogens, such as bacteria, viruses, and parasites. However, emerging research has revealed that the microbiome plays a crucial role in shaping host susceptibility to infections and influencing disease outcomes [4,5]. The microbiome interacts with pathogens directly or indirectly through various mechanisms, including competition for resources, production of antimicrobial substances, modulation of immune responses, and alteration in the local microenvironment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, these diseases have been attributed solely to pathogens, such as bacteria, viruses, and parasites. However, emerging research has revealed that the microbiome plays a crucial role in shaping host susceptibility to infections and influencing disease outcomes [4,5]. The microbiome interacts with pathogens directly or indirectly through various mechanisms, including competition for resources, production of antimicrobial substances, modulation of immune responses, and alteration in the local microenvironment [6].…”
Section: Introductionmentioning
confidence: 99%